Estudo toponímico dos nomes de bairros e ruas do Centro Histórico de Cuiabá 1701-2022 - Jesus, Ivanete Maria de (2023)
This research presents a study on the urban toponymy of the city of Cuiabá, the capital of the State of Mato Grosso, aiming to investigate, classify, and analyze the names of neighborhoods distributed across the four administrative regions (north, south, east, and west), as well as the streets within the Historic Center of the city of Cuiabá-MT, from the 18th to the 21st centuries. This interdisciplinary research is grounded in the field of Toponymy, a branch of Onomastics that focuses on the study of place names, as well as on revealing the cultural, ideological, and linguistic characteristics of human groups that have inhabited or currently inhabit a specific location. It also draws on Regional History studies to gather relevant information for understanding the denominations. Throughout the investigative process, the study seeks to address the following questions: What were the influences of the indigenous people and the Portuguese settlers who inhabited this area, on the features that still remain in the linguistic and extralinguistic fields, in the choices of neighborhood and street names in Cuiabá's Historic Center? What linguistic and extralinguistic factors motivated the creation of names for neighborhoods and streets in the Historic Center? What were the origin-related and historical processes behind the denominative causes of neighborhood and street names in the Historic Center? Which toponymic category had a greater prevalence in the naming of neighborhoods and streets in the capital's Historic Center: physical or anthropocultural taxonomies? The research is built upon the hypotheses that linguistic and extralinguistic factors could be reflected in place names and that there was an influence from linguistic strata directed either toward the indigenous language or Portuguese due to the colonization process. The research methodology involves the compilation, taxonomic classification, and analysis of toponyms, following the theoretical and methodological principles formulated by Dick (1990; 1996; 2004), with the intention of uncovering the potential causes behind the names in the Mato Grosso capital. The historical investigation of this study draws from documentary and field research, relying on documents and interviews to describe the socio-historical aspects, guided by the contributions of Silva (2012), Alencastro (2003), Romancini (2005), among others. In the field of Linguistics and Lexicology, the theoretical constructs of Biderman (1978-2001), Alves, and Isquerdo (2007) are particularly employed, with the aim to develop the Mato Grosso toponymic study. The findings show that among the 145 officially legislated toponyms of neighborhoods and streets in the capital, 56 are of physical nature and 89 are of anthropocultural nature, with the predominant toponymic motivation lying in the anthropocultural field, with higher productivity rates among historiotoponyms (17% of occurrences), axiotoponyms (13% of occurrences), and hagiotoponyms (12% of occurrences). This demonstrates that socio-historical and geographical aspects influence the naming of urban toponyms, particularly the practice of honoring individuals or commemorating regional and national historical dates. Furthermore, we observe the presence of hagiotoponyms, referring to the names of neighborhoods motivated by the religious life of the population of the capital of Mato Grosso. Regarding the morphological structure, toponyms with the highest productivity were those with hybrid compound structures, highlighting the role of the denominator in the naming process and within the linguistic strata, the primacy of the Portuguese language is evident. Based on these results, the analysis confirms that the prevailing factors in the designations are linked to the socio-historical and cultural aspects of the studied region, underscoring the importance of urban toponymy research as a significant form of linguistic and historical knowledge, contributing to the preservation of a people's memory through the naming of neighborhoods and streets.